Dalmatia in the Penitentiary Registers: The Periphery of Christendom? - Marinković, Ana (2004)
The notion of Dalmatia as periphery in the Middle Ages is examined in the context of two important practices: matrimonial contracts and trading with the "infidels". The Dalmatian source material from the records of the Holy penitentirary is compared to the matching material from the Central-Eastern Europe and Southern Europe.